Evaluasi Kualitas Layanan Situs Tiket.com Terhadap Kepuasan Pengguna Menggunakan Webqual dan Importance - Performance Analysis (IPA) - Nurjannah Nurjannah; Ari Kusyanti; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tiket.com is an online travel service that makes it easy for travelers to book ticket and hotel. This research was conducted to determine the quality of Ticket.com service from user perception by using Webqual 4.0, which has four dimensions, i.e; Usability, Information Quality, Service Interaction Quality, Satisfaction, Loyalty and Intention to Use and to know the quadrant of Importance - Performance Analysis (IPA) each webqual indicator. This study used data collection technique in questionnaire with large number of samples between 90-120 respondents, and got the number of respondents to be analyzed for 109. The result of this research concludes that variable of Usability, Information Quality, Service Interaction Quality have an effect to satisfaction, when user satisfaction is increasing it will influence to loyalty and intention to use the site. The results of the IPA quadrant show that the Performance indicator on the Usability variable has not satisfy the expectations of the user.